The Influence of Entrepreneurship Competence and Branding Capability on Business Performance (Universitas Terbuka, 2023)
This article discusses the market trend of coffee cafes as an emerging business which has implications for the increasing spread of coffee cafes in Indonesia. This has caused competition in coffee cafes today to become more competitive, and many of them need help to develop and compete so that coffee cafes go out of business. One of the strategies coffee cafes need to survive the dynamic competition and achieve business success through managerial is to implement entrepreneurial competence and branding capability. This study examines the influence of entrepreneurial competence and branding capability on business performance in coffee café Micro, Small and Medium Enterprises (MSMEs) in Jember Regency, East Java, Indonesia. This area is one of the archipelago's coffee producers from the Raung and Argopuro mountains. The research sample was obtained from identifying coffee cafes in the Jember Regency area through Google Maps based on a 4-5 star rating. Data was collected by distributing questionnaires to 39 coffee cafe managers and then analysed using multiple linear regression analysis. The results showed that entrepreneurial competence and branding capability simultaneously affect the business performance of coffee cafes. Partially, entrepreneurial competence has a positive and significant effect on coffee café business performance, while branding capability has no effect and is significant on coffee café business performance. The findings of this study also indicate that coffee café managers must develop their ability to manage business resources, expand networking for skills enhancement, and increase market share growth.